Pesquisa dos genes lipA e aprX em linhagens de Corynebacterium bovis, e seu crescimento sob refrigeração - Victória, Cassiano [UNESP]; Silva, Rodrigo Costa da [UNESP]; Romão, Felipe Gazza [UNESP]; Langoni, Helio [UNESP] (My University, 2011)
Some microorganisms frequently found in the raw milk of mastitics animals have the hability of multiplying in low temperatures, being called of psychotropic, and in this group, some have still the capacity to produce term steady enzymes that degrade proteins and fats, promoting relevant alterations in long periods stored milk. The present study aimed to determine if Corynebacterium bovis has the capacity to multiply in low temperature and if it had aprX and lipA genes, producing enzymes that degrade proteins and fats of the milk stored by long periods of time. The agent was incubated by 10 consecutive days in refrigeration, varying between 0.7 to 4ºC, and daily reading of absorbance (A) in spectrophotometer each 24 hours (M0 to M9 moments). The gene presence was accomplished with polimerase chain reaction (PCR). The results revealed that C. bovis is capable to multiply under refrigeration after 120 hours of incubation as observed between the moments M5 (A=0.264) and M6 (A=0.297) where P<0.05 confirming as psychotropic agent. In the other hand the studied microorganism doesn't possess the lipA and aprX genes, therefore it is not capable to produce the enzymes codified by these genes, what doesn't mean that C. bovis doesn't possess genes for the production of other degrading enzymes, don’t researched in the present study. This suggests that new studies of the genome of this microorganism are necessary, to elucidate this agent's true paper in the alteration of the quality of the milk and of their products.

Algunos microorganismos comúnmente encontrados en la leche cruda de animales mastíticos tienen la capacidad de multiplicarse en temperaturas de refrigeración, siendo llamados psicotróficos, y en este grupo, algunos aún tienen la capacidad de producir enzimas termoestables, que degradan proteínas y lípidos, promoviendo importantes alteraciones en la leche almacenada por longos períodos de tiempo. El presente estudio objetivó determinar si Corynebacterium bovis tiene la capacidad de multiplicarse en temperatura de refrigeración y si tiene los genes aprX y lipA, productores de enzimas que degradan proteínas y gorduras de la leche almacenada por longos períodos de tiempo. El agente fue incubado en 0,7 y 4ºC, por 10 días consecutivos, con la aferición de los valores de absorbencia (A) en espectrofotómetro por cada 24 horas (momentos M0 hasta M9). Para la verificación de la presencia de los genes fue realizada la reacción en cadena por la polimerasa (PCR). Los resultados revelaron que C. bovis puede multiplicarse en refrigeración después de 120 horas de incubación donde hubo diferencia significante con P<0,05 entre los períodos M5 (A=0,264) y M6 (A=0,297) considerado psicotrófico. Por otro lado, no tiene los genes aprX y lipA, no produciendo las enzimas codificadas por estos genes, lo que no significa que C. bovis no tiene genes para la producción de otras enzimas degradantes, no pesquisadas en el presente estudio. Eso sugiere que nuevos estudios del genoma de este microorganismo son necesarios para elucidar el verdadero papel de este agente en la alteración de la calidad de la leche y de sus subproductos.

Alguns micro-organismos comumente encontrados no leite cru de animais mastíticos possuem a capacidade de se multiplicar em temperaturas de refrigeração, sendo denominados de psicrotróficos, e neste grupo, alguns têm ainda a capacidade de produzir enzimas termoestáveis, que degradam proteínas e lipídeos, promovendo alterações importantes no leite armazenado por longos períodos de tempo. O presente estudo objetivou determinar se Corynebacterium bovis possui a capacidade de se multiplicar em temperatura de refrigeração e se possui os genes aprX e lipA, produtores de enzimas que degradam proteínas e gorduras do leite armazenado por longos períodos de tempo. O agente foi incubado a 0,7 e 4ºC, por 10 dias consecutivos, com a aferição dos valores de absorbância (A) em espectrofotômetro a cada 24 horas (momentos M0 à M9). Para a verificação da presença dos genes foi realizada a técnica da reação em cadeia pela polimerase (PCR). Os resultados revelaram que C. bovis é capaz de se multiplicar sob refrigeração após 120 horas de incubação onde houve diferença significante com P<0,05 entre os períodos M5(A=0,264) e M6(A=0,297) considerado-o como psicrotrófico. Por outro lado, não possui os genes aprX e lipA, não produzindo as enzimas codificadas por estes genes, o que não significa que o C. bovis não possua genes para a produção de outras enzimas degradantes, não pesquisadas no presente estudo. Isto sugere que novos estudos do genoma deste micro-organismo são necessários, para se elucidar o verdadeiro papel deste agente na alteração da qualidade do leite e de seus subprodutos.
Research for lipA and aprX genes in Corynebacterium bovis samples, and its growth under refrigeration
Presencia de los genes lipA y aprX en muestras de Corynebacterium bovis, y su desarrollo en refrigeración
Keywords: Corynebacterium bovis; Mastitis; aprX; lipA; Growth; Corynebacterium bovis; Mastitis; aprX; lipA; Corynebacterium bovis; Mastites; aprX; lipA; Crescimento